A Systematic Review of Controlled Trials Evaluating Interventions Following Non-Marital Relationship Separation. (6th March 2017) - Kazan, Dominique; Calear, Alison L.; Batterham, Philip J.
Abstract : The effect of a relationship separation on wellbeing is substantial. However, without divorce parameters, individuals in dating or cohabiting relationships may struggle to access support mechanisms. A systematic review was conducted to identify controlled trials of interventions targeting individuals who have experienced a non-marital relationship separation, to supplement the divorce literature. The aim of the review was to assess the impact of these interventions on mental health. Five articles were identified through PsycINFO, PsycARTICLES and Medline databases. Overall, two of the trials reported a significant improvement in specific mental health outcomes at post-test and/or follow-up. Of the two trials demonstrating efficacy in mental health outcomes, one used a weekly, forgiveness-based group intervention and the other was a writing-based, self-initiated intervention. A lack of trials testing theory-driven interventions for relationship separation is of particular concern. Limitations of the existing literature and corresponding directions for future research are discussed.